Hohfeld, Berlin and the Social Dimensions of Rights of Conscience in Health Care. - May, Thomas (American Journal of Bioethics, 2026)
The article critically examines the proposal to use claims of conscience in healthcare as a means to circumvent ethical dilemmas related to harm, futility, and best interests. It argues that while conscience claims may address legal concerns, they do not resolve the underlying moral complexities, which require balancing the rights of healthcare providers with those of patients within the "special relationship" of care. The author emphasizes that rights of conscience must be exercised consistently with corresponding duties, avoiding discrimination and respecting patients' reasonable expectations of access to standard care. Ultimately, the article contends that leveraging conscience claims cannot replace thorough ethical analysis of harm, futility, and patient interests in healthcare decision-making.